2020
DOI: 10.1002/onco.13586
|View full text |Cite
|
Sign up to set email alerts
|

Navigating Diagnostic and Treatment Decisions in Non-Small Cell Lung Cancer: Expert Commentary on the Multidisciplinary Team Approach

Abstract: Non‐small cell lung cancer (NSCLC) accounts for approximately one in five cancer‐related deaths, and management requires increasingly complex decision making by health care professionals. Many centers have therefore adopted a multidisciplinary approach to patient care, using the expertise of various specialists to provide the best evidence‐based, personalized treatment. However, increasingly complex disease staging, as well as expanded biomarker testing and multimodality management algorithms with novel therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 77 publications
(93 reference statements)
1
30
0
2
Order By: Relevance
“…This approach reduces time wasted for travel to reach the referral center and shortens the time to case evaluation [13]. Such a collaborative strategy strongly depends on efficient and effective communication between vMTB team members [14]. To be efficient and effective, vMTB requires a collaborative approach, appropriately leveraging the diverse expertise of LC.…”
Section: Board Virtualization and Telemedicinementioning
confidence: 99%
See 1 more Smart Citation
“…This approach reduces time wasted for travel to reach the referral center and shortens the time to case evaluation [13]. Such a collaborative strategy strongly depends on efficient and effective communication between vMTB team members [14]. To be efficient and effective, vMTB requires a collaborative approach, appropriately leveraging the diverse expertise of LC.…”
Section: Board Virtualization and Telemedicinementioning
confidence: 99%
“…Some evidence suggests that implementing MDT discussions improves patients' outcomes, i.e., pretreatment evaluation, proper staging, adequate treatment, quality of survivorship, and overall survival [12][13][14]. Specchia et al very recently reported an umbrella review on MTB's impact on all types of cancer, reporting only one systematic review on LC published several years ago in 2008 [13,14]. However, Australian researchers recently published a scoping review of current evidence for LC-MDT data collection and analysis and its impact on clinical outcome [16][17][18].…”
Section: Impact On Clinical Outcomesmentioning
confidence: 99%
“…Treatment modalities for stage I-IIIA NSCLC are heterogeneous requiring cooperation between many specialties. A MDT approach involving all those involved in a patient's treatment is key to establishing the need for molecular testing, developing any regional or institutional algorithm, and coordinating molecular testing [60,61]. Communication between specialties is vital to avoid delays and reduce unnecessary procedures and pathology tests, and is also helpful to communicate the adequacy of the sample, status of molecular testing, and the testing results to all specialists involved in the care of an individual patient.…”
Section: Multidisciplinary Team (Mdt) Approachmentioning
confidence: 99%
“…This approach reduces time wasted for travel to reach the referral center and shortens the time to case evaluation [13]. Such a collaborative strategy strongly depends on efficient and effective communication between vMTB team members [14]. To be efficient and effective, vMTB requires a collaborative approach, appropriately leveraging the diverse expertise of LC.…”
Section: Board Virtualization and Telemedicinementioning
confidence: 99%